Competition and Contestability in Malaysian Banking Market - Rossazana, Ab. Rahim; Nor Ghani, Md. Nor; Shamsubaridah, Ramlee; Lo, May Chiun (Asian Economic Review Journal, 2011)
At the one hand, the market structural reform through mergers and acquisitions in the banking industry leads to a reduction in number of banks operating in the industry, thus enhance the level of concentrated market which results in lower banking competition. On the other hand, there is no clear evidence that in more concentrated markets, the competition is lower. The contestable market theory by Baumol (1982) emphasizes that a high concentrated banking market can be highly competitive even if it is dominated by few dominant banks. By addressing the above discussion as the gap in the literature, it is interesting to investigate whether the increased concentration hampers the realization of banking competition or whether the increased market concentration turns the banking industry to be more competitive. The results of this study found that structural reform in Malaysian banking industry is not translated into the increasing trend of market concentration. In addition, the results of H-statistics reveal that banks in Malaysian banking are operating under monopolistic competition. Nevertheless, the results do not support to the contention that high concentration in banking market will hamper the banking competition. _____________